Protocol for assessing the clogging of the mitochondrial translocase of the outer membrane by precursor proteins in human cells - John Kim; Hilla Weidberg (STAR Protocols)
Summary: Protein import into the mitochondria is required for organellar function. Inefficient import can result in the stalling of mitochondrial precursors inside the translocase of the outer membrane (TOM) and blockage of the mitochondrial entry gate. Here, we present a protocol to assess the clogging of TOM by mitochondrial precursors in human cell lines. We describe how the localization of mitochondrial precursors can be determined by cellular fractionation. We then show how co-immunoprecipitation can be used to test the stalling of precursors inside TOM.For complete details on the use and execution of this protocol, please refer to Kim et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.